A CROSS‐LAGGED MODEL OF THE DEVELOPMENT OF MENTOR–MENTEE RELATIONSHIPS AND INTENTIONAL SELF‐REGULATION IN ADOLESCENCE. Issue 1 (January 2016) - Bowers, Edmond P.; Wang, Jun; Tirrell, Jonathan M.; Lerner, Richard M.
Abstract : Intentional self‐regulatory, or goal‐directed, skills are essential for positive social relationships, success, and well‐being during adolescence. Prior theory has suggested that mentoring relationships may provide a key resource for building these skills. However, there is little direct evidence linking mentoring relationships to growth in youth intentional self‐regulation (ISR). Accordingly, we examined the bidirectional relations between mentor–mentee relationship and ISR using data from 415 mentor–mentee dyads from programs around the United States. The 415 youth (48% female) ranged in age from 10.14 to 20.65 and were ethnically and socioeconomically diverse. The 114 mentors (58.8% female; 64% Caucasian) were, on average, 33.6 years of age. Results from cross‐lagged structural equation modeling indicated that a latent factor of mentor–mentee relationship predicted growth in a latent factor of youth ISR. These findings support the role of mentors in promoting youth ISR. The implications of these findings for the training of practitioners are discussed.